The LAND RESOURCES MANAGEMENT ACCORDING TO AGRARIAN LAND ZONING - Alona IUKHNO (Modern Management Review, 2023)
Management of land resources as a state system of measures is aimed at providing the population with food and other branches of the national economy with raw materials at the optimal level of capital investments in resources and their maximum return under the conditions of compliance with environmental goals and programs to ensure the norms and requirements of the rational use of land by agricultural enterprises with the aim of obtaining an ecologically clean plant and animal products while preserving natural resources. It is proposed to manage land resources of agricultural enterprises based on indicators of agricultural zoning, which provides information on zoned crops and types of crop rotation that are most suitable for growing on the territory of a specific agricultural enterprise, the implementation of technological measures for the use and protection of land, the level of influence of these measures on productivity and efficiency land use by an agricultural enterprise.